(untitled) (Hoplos - Revista de Estudos Estratégicos e Relações Internacionais, 2023)
This paper has the following research question: Why hasn’t Brazil further advanced the Responsibility while Protecting (RwP) agenda and, instead, eventually abandoned its proactive instance on the matter? The investigation is based on a qualitative approach which aims to deepen the debate around RwP, the Brazilian interests in the security area, especially the pursuit of a permanent seat in the UN Security Council, and the reasons and implications behind the abandonment of that proposal. While multiple explanations have been brought up, this paper discusses the hypothesis that the moderation of the country’s ambitions, particularly in the security field, played a fundamental role in the change of the Brazilian behaviour towards the RwP.